Reduction in mitochondrial iron alleviates cardiac damage during injury - Hsiang‐Chun Chang; Rongxue Wu; Meng Shang; Tatsuya Sato; Chunlei Chen; Jason S Shapiro; Ting Liu; Anita Thakur; Konrad T Sawicki; Sathyamangla VN Prasad; Hossein Ardehali (EMBO Molecular Medicine)
Abstract Excess cellular iron increases reactive oxygen species (ROS) production and causes cellular damage. Mitochondria are the major site of iron metabolism and ROS production; however, few studies have investigated the role of mitochondrial iron in the development of cardiac disorders, such as ischemic heart disease or cardiomyopathy (CM). We observe increased mitochondrial iron in mice after ischemia/reperfusion (I/R) and in human hearts with ischemic CM, and hypothesize that decreasing mitochondrial iron protects against I/R damage and the development of CM. Reducing mitochondrial iron genetically through cardiac‐specific overexpression of a mitochondrial iron export protein or pharmacologically using a mitochondria‐permeable iron chelator protects mice against I/R injury. Furthermore, decreasing mitochondrial iron protects the murine hearts in a model of spontaneous CM with mitochondrial iron accumulation. Reduced mitochondrial ROS that is independent of alterations in the electron transport chain's ROS producing capacity contributes to the protective effects. Overall, our findings suggest that mitochondrial iron contributes to cardiac ischemic damage, and may be a novel therapeutic target against ischemic heart disease.